Types of poetry figures (shabdalankar) of Mira Bai's poetry: DOI: https://doi.org/10.17721/1728-242X.2020.26.55-57 (BULLETIN OF TARAS SHEVCHENKO NATIONAL UNIVERSITY OF KYIV. ORIENTAL LANGUAGES AND LITERATURES, 2023)
This article addresses the issue of the types of poetic figures (shabdalankar) in the poetry of the famous poetess of the medieval socio-religious movement bhakti Mira Bai, namely, an important category of Hindi poetry – alankars, which help to express aesthetic emotion – racu. Therefore, their study is of great importance for characterizing the work of Mira Bai in general. Alankars are usually called rhetorical figures, and their close translation – "decorations" – corresponds to the most important European rhetorical category fully, which covers the concept of figures and paths ornatus. They adorn the sound and meaning of the word and help to show aesthetic emotion – racu. It was suggested to study the types of shabdalankar (form decorations) in the poetry of Mira Bai. It was reviewed such shabdalankars as anupras (alliteration), yamaka (lexical repetition – "consonance"), vacrocti and shlesha (some types of paronomasia – "combination"). It was found that in the verses of Mira Bai there are mainly two of them – anupras and vipsa. A feature of the formal side of Mira Bai's works is miserly use of poetry adornments, since the poetry's verses are a cry of the soul, they reflect the unbearable pain of separation from her beloved Krishna. In such a state of mind, Mira Bai was not up to artificial decoration and play on words. If individual alancars appear in her poetry, it happens completely at ease. Only one of several shabdalankar dominates in the verses of Mira Bai, namely: anuprasa, which helps the poetess through the melody of the verse to create the mood she needs and clearly show the aesthetic emotion of love – the shringar's racu.
Keywords: alancara; anuprasa; vipsa; shlesha; yamaka